Identifying faculty opinions about implementing an online, non-thesis master’s degree - Maynard, Rebekah C. I.; Pennisi, Svoboda V.; Lombardini, Leonardo (Frontiers in Education, 2023)
Introduction Although distance education is a growing field, there are benefits and challenges in creating and implementing new online degrees. Faculty play a critical role in forming new online programs and hold differing perceptions about online learning. The purpose of this research was to identify faculty opinions about implementing an online, non-thesis master’s degree as an alternative to the existing thesis-based degree. Methods In this study, 17 faculty members in the field of horticulture were surveyed at a major university in the southeastern United States. Q methodology was selected as the research tool to identify the primary opinions faculty held about an online, non-thesis master’s degree. Once participants were surveyed, factor analysis was used to reduce the responses into three perspectives. Results Three distinct perspectives were summarized as: (A) in-person instruction is more effective than online education, (B) online programs increase accessibility to graduate degrees, and (C) successful online programs require independent learners. Participants holding the first perspective believed an online program would not benefit student learning and would increase the workload of faculty. Participants with perspectives B and C agreed that an online program would be beneficial in reaching a broader audience of students. Although perspective C placed a high importance on independent learning, perspectives A and B indicated engaging with students was critical to student learning. Discussion All factors agreed an online degree would help our department reach non-research-oriented students. However, there was discrepancy in faculty willingness to support the program. Based on the identified faculty perspectives, it is believed that an online, non-thesis master’s would be successful if faculty who are willing to participate in the online degree were trained to be effective online educators and if they encouraged students to hold a deeper level of engagement with the content.